A review of biodegradability of natural rubber products: Physicochemical, thermal and mechanical properties - Tong, Hui Shan; Siti Maznah, Kabeb; Hazrulrizawati, Abd Hamid; Farah Hanani, Zulkifli (Elsevier Ltd, 2025)
Natural rubber latex (NRL) is a biopolymer consisting of isoprene monomers in a cis configuration connected by double bonds that can degrade naturally. Most natural rubber (NR) based products are single-use items and its microbial degradation process is relatively slow. Hence, this review highlights the importance in the enhancement of biodegradation of NR, the methods applied to increase the biodegradation rate, and characterization of biodegradation of rubber. The biodegradability of NR-based products is enhanced via selective microorganism strains, suitable composting environment and the addition of biofillers. Rubber oxygenase enzymes and latex cleavage protein are major contributors in the biodegradation of NR-based products, while biofillers such as chitosan, cellulose whiskers and starch enhances biodegradation rate up to 60 %. Biodegradation of NR-based products is confirmed through characterization of physicochemical, thermal and mechanical properties using SEM, XRD, FTIR, GPC, TGA, UTM, physical appearance and weight loss. NR-based materials with enhanced biodegradability have many uses, thus its customizability should be studied further in terms of different product forms, fabrication method, orientation of biofiller used and incorporation of metal organic frameworks.